The evaluation of simultaneous combined surgery of the heart and thyroid - own experience - Gniłka, Andrzej; Gniłka, Włodzimierz; Juraniec, Olga; Pawliszak, Wojciech; Anisimowicz, Lech; Junik, Roman (Journal of Education, Health and Sport, 2024)
Background: Patients referred for cardiac surgery usually also have other comorbidities. These include thyroid disease, which is relatively common in patients with heart problems. Objective: The aim of the study was to evaluate the feasibility of combined cardiac surgery and thyroidectomy. Material and methods: Six patients (age range: 54-74 years) qualified for elective, simultaneous surgeries on the heart and the thyroid were included in the study. In preparation for thyroidectomy, three patients were diagnosed with diseases requiring cardiac surgery. Two patients, initially referred for coronary artery bypass surgery in one case, and surgery for recurrent fluid in the pericardial sac with concomitant mitral and tricuspid valve regurgitation and atrial fibrillation in the other, were diagnosed in large hyperactive goitre. The last patient with a history of oncology (lung tumour), admitted to the Department of Cardiology due to a heart attack, had a CT scan of the chest, which revealed retrosternal goitre narrowing the lumen of the trachea to 9 mm. All patients underwent combined heart and thyroid operation and were discharged home 8-27 days after surgery. Conclusions: Although preoperative qualification requires a very cautious and individual approach, simultaneous surgeries in patients requiring thyroid and heart interventions are expedient and should be promoted.